A method to construct graphs with certain partition dimension - Debi Oktia Haryeni; Edy Tri Baskoro; Suhadi Wido Saputro (Electronic Journal of Graph Theory and Applications (EJGTA), 2019)
In this paper, we propose a method for constructing new graphs from a given graph G so that the resulting graphs have the partition dimension at most one larger than the partition dimension of the graph G. In particular, we employ this method to construct a family of graphs with partition dimension 3.